Casa de niebla - Bombal, María Luisa, 1910-1980 (Ediciones UC, 2012)
Casa de Niebla opens with a warning: "There will be no murder or assassin, but there will be a crime." Set in the early days of the 20th century, this no-candle tells the story of Helga in a mansion surrounded by fog, while Teresa's ghost appears every night haunting the waters of the lagoon. This creates the atmosphere of a novel full of shadows and mysteries for the protagonist, who experiences unrequited love and ventures into dreamlike reality. Written in the forties, the gothic aesthetic is elaborated using cinematographic techniques of that time in the peculiar style of María Luisa Bombal. The crime deciphered through the detective format throws clues about an adultery that ironically goes unpunished. And in contrast, the supernatural - life beyond death - is presented as that which does not admit rational investigations. Published in 1947 in English under the title House of mist and translated to date into French, Swedish, Portuguese and Japanese, after sixty-five years Spanish-speaking readers can access the only unpublished work in Spanish by one of the greatest Chilean and Latin American writers of the 20th century.